Evaluation of the strength of the upper extremity and the balance in pediatric population with hemiplegia after stroke - Katsantoni, Dimitra; Anna, Chalkia; Giorgos, Tsigaras; Thomas, Besios; Lefteris, Klonos (International journal of health sciences, 2024)
Introduction: The brain is a system with multidimensional organization and architecture and requires a continuous blood supply to function normally. If blood flow is interrupted for more than a few seconds, the brain is deprived of blood and oxygen, causing death in nerve cells in the affected area. The stroke in children after birth appears even more rarely than in adults. Methods: For the study, 20 children with hemiplegic cerebral palsy (14 boys and 6 girls) participated (mean age 10,9 years), from the “General Hospital Hippocratio” of Thessaloniki, according to the inclusion criteria. The strength of the upper extremity was measured using the Jamar dynamometer. To assess the balance, the Pediatric Balance Scale (PBS) Affected and contralateral hands results were analyzed and compared with norms for age and sex and related to the affected balance. Results: It was found that the strength of the non-affected upper extremities was also reduced according to the data of the normal children and the balance was also affected because of the stroke. Discussion: Physiotherapy programs may include exercises that emphasize the non-affected upper extremities, more similar research must be done on a bigger population.